2013
DOI: 10.1177/0040517513512399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wind and clothing apertures on local clothing ventilation rates and thermal insulation

Abstract: The purpose of this study was to investigate the effects of wind (0 m/s, 1.1 m/s) and clothing apertures (no close, close hem, close hem and neck) and the combined effects of them on local clothing ventilation rates and localized thermal insulation. Nine working jackets with identical design but different garment sizes and fabric permeability were made. The results showed that wind and clothing apertures had distinct effects both on the local ventilation rates and the local thermal insulation. The local ventil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
0
27
0
3
Order By: Relevance
“…The results showed that adding fullness in the T-shirt design can significantly reduce the thermal and water vapor resistance of T-shirt. Ke, Havenith, Zhang, Li, and Li (2013) investigated the effects of clothing apertures on ventilation rates and thermal insulation. The results showed that clothing apertures had distinct effects both on the local ventilation rates and the local thermal insulation.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that adding fullness in the T-shirt design can significantly reduce the thermal and water vapor resistance of T-shirt. Ke, Havenith, Zhang, Li, and Li (2013) investigated the effects of clothing apertures on ventilation rates and thermal insulation. The results showed that clothing apertures had distinct effects both on the local ventilation rates and the local thermal insulation.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] The main reason is that clothing microclimate ventilation helps in removing the sensible and latent heat of the human body. 5 For decades, research has focused on developing predictive empirical or theoretical models of the clothing ventilation. 8,9 However, this focus was mainly on estimating the overall clothing ventilation that affects the overall thermal comfort state of the wearer.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we focus upon the use of the IP SPM tool to assess the relative importance of changing the air flow resistance of fabric layers or permeable vent sections upon the calculated total heat transfer resistance of the clothing system. Several recent experimental papers have discussed the tradeoffs between fabric air flow resistance, clothing vents, and the interaction with air flow due to external wind or body motion [4][5][6].…”
Section: Introductionmentioning
confidence: 99%